Clinical and investigative profile of scrub typhus patients at a tertiary care center in Southern West Bengal, India - Kalyan Kumar Bhowmik; Sarkar, Amit; Arpan Chakrabarti; Neelakash Mukhopadhyay; Arnab Paul (Asian Journal of Medical Sciences, 2024)
Background: Scrub typhus, caused by Orientia tsutsugamushi, is an acute febrile illness with symptoms such as fever, chills, and organ failure. The similar clinical presentation in other common diseases such as malaria, dengue fever, and typhoid fever creates difficulty and delay in the clinical diagnosis of scrub typhus. This delay may increase the risk of scrub typhus complications. In India, it is a public health issue with a paucity of data. Aims and Objectives: This study aims to evaluate the clinical characteristics, outcomes, and prognostic factors of patients with scrub typhus. Materials and Methods: This institutional-based observational, cross-sectional study was conducted among consecutively selected 154 adult patients suffering from scrub typhus at a Medical College Hospital situated in the southern part of West Bengal, India. All data were collected according to a pre-designed proforma. At the end of the study, results were analyzed statistically. Results: Younger, females, and homemakers are more susceptible to scrub typhus, mostly in the post-monsoon season from July to November. The incidence of scrub typhus complications is high in the southern part of West Bengal. The case fatality rate of scrub typhus is 6.5%. Male sex, pre-hospitalization duration of illness more than 7 days, presence of diabetes mellitus, serum creatinine (Scr) more than 1.5 mg/dL, serum bilirubin more than 3 mg/dL, systolic blood pressure below 90 mmHg, altered sensorium, and acute respiratory distress syndrome were associated with poor prognosis. Conclusion: A high degree of clinical suspicion is required for the early diagnosis of scrub typhus and the factors associated with poor prognosis must be considered to reduce morbidity and mortality.